2018
DOI: 10.1093/nar/gky581
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule tracking reveals that the bacterial SMC complex moves slowly relative to the diffusion of the chromosome

Abstract: Structural Maintenance of Chromosomes (SMC) proteins and their complex partners (ScpA and ScpB in many bacteria) are involved in chromosome compaction and segregation in all kinds of organisms. We employed single molecule tracking (SMT), tracking of chromosomal loci, and single molecule counting in Bacillus subtilis to show that in slow growing cells, ∼30 Smc dimers move throughout the chromosome in a constrained mode, while ∼60 ScpA and ScpB molecules travel together in a complex, but independently of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 64 publications
6
32
0
Order By: Relevance
“…1C), showing further that Smc foci apparently do not always colocalize with origin foci (we found colocalization in 43.4% of foci) and revealing that Smc is also statically bound to DNA away from origin regions. This is consistent with chromatin immunoprecipitation with microarray technology (ChIP-chip) data revealing Smc enrichment at several sites away from oriC (20) and with the results of our previous SMT experiments (8).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1C), showing further that Smc foci apparently do not always colocalize with origin foci (we found colocalization in 43.4% of foci) and revealing that Smc is also statically bound to DNA away from origin regions. This is consistent with chromatin immunoprecipitation with microarray technology (ChIP-chip) data revealing Smc enrichment at several sites away from oriC (20) and with the results of our previous SMT experiments (8).…”
Section: Resultssupporting
confidence: 92%
“…Previously, Smc had been described to be clustered around oriC regions, forming foci that colocalize with oriC and with ParB foci. However, using single-molecule tracking, we recently found that Smc forms immobile clusters at many sites on the chromosome (8). To clarify this issue, we constructed a strain in which a functional Smc-mVenus (Smc-mVenus fluorescent protein) fusion can be localized relative to origin regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5E ). Interestingly, the diffusion constant for the fast subpopulation of AbrB (total mass of 156 kDa including YFP) is very similar to the diffusion constant of 0.53 µm 2 /s for the freely diffusive fraction of the Smc dimer 33 (total mass of 330 kDa including YFPs), and 0.51 µm 2 /s for the freely diffusive fraction of the DnaA dimer 9 (total mass of 156 kDa including YFPs), suggesting that this corresponds to the freely diffusive state of AbrB. In contrast, the previously reported diffusion constant for the DNA-bound state of Spo0J (0.02 µm 2 /s) 9 is about 4-fold lower than that for the static subpopulation of AbrB (0.084 µm 2 /s), suggesting that this value might be the result of a mixture between two diffusive states, for instance by AbrB frequently interacting with DNA in a non-specific manner, in search of its binding sites.…”
Section: Resultsmentioning
confidence: 62%
“…We next turned towards SMT to quantify changes in protein dynamics at a single molecule level, using an experimental setup that has been described before (43,45,46). We used SMTracker software 1.5 (36) to analyse tracks that were generated using u-track software (33).…”
Section: Single Molecule Tracking Reveals Poor Enrichment Of Dnag At mentioning
confidence: 99%